2016
DOI: 10.21767/2471-982x.100013
|View full text |Cite
|
Sign up to set email alerts
|

Single Needle Thoracic Paravertebral Block with Ropivacaine and Dexmeditomidine for Radical Mastectomy: Experience in 25 Cases

Abstract: Background: Currently regional technique like thoracic paravertebral block for breast surgery is gaining a lot of popularity. As it produces unilateral action thereby minimal hemodynamic changes with autonomic blockade, allows early ambulation, facilitates postoperative analgesia, eliminate the risks/complications of general anaesthesia and thus reduces the hospital stay and cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Furthermore, it is associated with minimal hemodynamic instability, early discharge from hospital with reduced cost of the treatment. 5 In almost all of these cases, the block was performed under ultrasound guidance which benefits of direct visualization of the needle, local anesthetic (LA) spread and the pleura. Besides, in some of the cases, a continuous epidural catheter was inserted into the paravertebral space.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, it is associated with minimal hemodynamic instability, early discharge from hospital with reduced cost of the treatment. 5 In almost all of these cases, the block was performed under ultrasound guidance which benefits of direct visualization of the needle, local anesthetic (LA) spread and the pleura. Besides, in some of the cases, a continuous epidural catheter was inserted into the paravertebral space.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies also suggested that TPVB attenuates perioperative immunosuppression and decrease cancer metastasis. 1 , 5 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thoracic paravertebral space contains dorsal and ventral rami of spinal nerves, sympathetic chain where injection of local anaesthetic is made that produces unilateral sympathetic, sensory and motor blockade [2,3]. We conducted a study on sole TPVB for radical breast surgeries in 25 ASA grade I-III patients and found it is very safe and useful method [4]. We intend to report a recent high risk case of 92 years old lady with compromised cardiopulmonary function who underwent radical mastectomy under sole TPVB successfully.…”
Section: Introductionmentioning
confidence: 99%